Análise da citotoxicidade e do grau de conversão de resinas compostas de metacrilato e de silorano - Virginia Angelica Silva (2012)
The composite based Silorane come with good mechanical results in several laboratory studies, but the knowledge about their effects on cells of the gingival tissue and the degree of conversion is not well established yet. The objective of this study was to evaluate cell viability and degree of conversion of a composite resin base silorane (Filtek P90 3M ESPE) and three conventional methacrylate resins (Filtek Z350XT 3M ESPE, Filtek Z100 3M ESPE and Filtek Z250 3M ESPE), all light-cured for 20 and 40 seconds with LED light curing unit (Flash lite DISCULS), in primary cultures of gingival fibroblasts. We also assessed the possibility of a correlation between the degree of conversion and the cell viability. For this purpose six specimens (n = 6) of each composite were prepared from a mold. Cellular metabolism was evaluated after 24 hrs by MTT test (metiltetrazólio), in witch 1.5 x105 cells/well were seeded in 96-well plates and, after 48 hours, placed in contact with the storage medium from the preincubation specimens of composite resin for 24 hours or 12 days. The degree of conversion was analyzed by FTIR test Fourier transform and the analysis of variance (ANOVA) with Bonferroni correction (p <0.05) was performed to compare the groups. The research showed that only the resin Filtek Z100 was cytotoxic when photocured in both studied periods and the variation in time of incubation of the composite did not alter the cellular viability. Regarding the degree of conversion, Filtek Z250 was the composite with the lowest value and Filtek P90 the one with the highest. The composites Filtek Z100 and Filtek P90 showed higher degree of conversion when polymerized for 40s than 20s, whereas the composites Filtek Z250 and Filtek Z350XT showed no differences. We found no statistically significant correlation between cell viability and degree of conversion.